Yksinäinen mies ; Aamu vie aamu tuo - Niemi, Jani, 1971-; Power Records (Lahti : Power Records, 1999)
2 kappaletta.
Jani Niemi (lauluääni), yhtye.
Keywords: Niemi, Jani, -- 1971- -- singlet; viihdemusiikki